2018
DOI: 10.1182/blood-2017-09-805762
|View full text |Cite
|
Sign up to set email alerts
|

Biased IGH VDJ gene repertoire and clonal expansions in B cells of chronically hepatitis C virus–infected individuals

Abstract: Patients chronically infected with hepatitis C virus (HCV) frequently develop mixed cryoglobulinemia (MC), a monoclonal expansion of immunoglobulin M (IgM) autoreactive B cells, and also have an increased B-cell lymphoma risk. Whether HCV infection also impacts the B-cell compartment and the B-cell receptor repertoire in patients not affected by MC or lymphomas is poorly understood. Flow cytometric analysis of peripheral blood B cells of 30 MC-negative HCV-infected patients and 15 healthy controls revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
6
27
0
Order By: Relevance
“…Blum et al [102] identified preferential usage of certain IGHV segments in the plasmablast repertoires of Lyme disease patients. Tucci et al [103] reported disrupted B-cell repertoires in a cohort of chronic HCV patients due to preferential usage of several IGHV segments in IGM memory B-cells. While CDR3 may be conserved within a subset of antigen-specific sequences, even withinTCRs recognizing one epitope, there are frequently many distinct motifs, each successfully solving the task of antigen recognition [47,104].…”
Section: Clonal Sequence Featuresmentioning
confidence: 99%
“…Blum et al [102] identified preferential usage of certain IGHV segments in the plasmablast repertoires of Lyme disease patients. Tucci et al [103] reported disrupted B-cell repertoires in a cohort of chronic HCV patients due to preferential usage of several IGHV segments in IGM memory B-cells. While CDR3 may be conserved within a subset of antigen-specific sequences, even withinTCRs recognizing one epitope, there are frequently many distinct motifs, each successfully solving the task of antigen recognition [47,104].…”
Section: Clonal Sequence Featuresmentioning
confidence: 99%
“…A major risk factor specific to SOT is the use of multivisceral or intestinal transplants due to a high volume of donor lymphoid tissue contained in the graft, which is subject to expansion when exposed to EBV and in an immunodeficient environment (Kinch et al , ). Although an intact immune system is essential for chronic viral hepatitis to directly cause a lymphoproliferative disorder, untreated infection with the hepatitis C virus can contribute to PTLD pathogenesis by inducing alterations in the B‐cell receptor immunoglobulin gene and through chronic antigenic stimulation (Morton et al , ; Tucci et al , ). Recipient HLA‐A26 and HLA‐B38 status has also been associated with a higher risk, probably due to altered antigen presentation or immune tolerance (Reshef et al , ).…”
Section: Epidemiologymentioning
confidence: 99%
“…The B cell receptor (BCR), a B cell surface membrane immunoglobulin, possesses the ability to specifically recognize and bind antigens, with the complementarity-determining region 3 (CDR3) of the heavy chain as the major determinant of antibody specificity (Xu and Davis, 2000). The diversity of BCR repertoires in several infectious diseases has been explored, such as in coronavirus disease 2019 (Wen et al, 2020), dengue (Parameswaran et al, 2013), and chronic hepatitis C virus infection (Tucci et al, 2018). These results show that encountering a specific antigen could elicit clonal B-cell proliferation, thus altering the selective distribution of the BCR spectrum.…”
Section: Introductionmentioning
confidence: 99%